Identification of Differentially Expressed cDNA in Cassava under Drought Stress Using cDNA-RAPD Approach - Hartati, N. Sri; Supatmi, Supatmi; Aryaningrum, Pramesti Dwi; Sudarmonowati, Enny (BRIN, 2013)
Cassave is an important carbohydrate